Distribution. N in Sciuridae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Distribution. N Alaska, in the Brooks Range from Chukchi Sea coast to the Alaska-Yukon border in Canada. Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Sciuridae, pp. 648-837 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 820, DOI: 10.5281/zenodo.6840226